2008
DOI: 10.1210/jc.2007-2733
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Strength and Endurance Training on Insulin Sensitivity and Fat Distribution in Human Immunodeficiency Virus-Infected Patients with Lipodystrophy

Abstract: This study demonstrates that both strength and endurance training improve peripheral insulin sensitivity, whereas only strength training reduces total body fat in HIV-infected patients with lipodystrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
141
0
32

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(180 citation statements)
references
References 43 publications
7
141
0
32
Order By: Relevance
“…Some studies, such as those by Mutimura et al 9 , Robinson et al 10 , Lindegaard et al 11 , Terry et al 12 and Thoni et al, 13 have suggested that regular exercise is beneficial for people living with HIV/AIDS. They also reported a decrease in the excessive accumulation of trunk body fat and improvement in the metabolic variables related to it, which suggests that there is a valid alternative for the treatment of lipodystrophy.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies, such as those by Mutimura et al 9 , Robinson et al 10 , Lindegaard et al 11 , Terry et al 12 and Thoni et al, 13 have suggested that regular exercise is beneficial for people living with HIV/AIDS. They also reported a decrease in the excessive accumulation of trunk body fat and improvement in the metabolic variables related to it, which suggests that there is a valid alternative for the treatment of lipodystrophy.…”
Section: Discussionmentioning
confidence: 99%
“…Como meio de atenuar esses efeitos destacar-se a prática da atividade física, em que a mesma pode contribuir na melhora da autoestima 6,7 , da força muscular 8,9 , do sistema imune 10 , dos marcadores bioquímicos, da massa muscular 8,11,12 , do sistema cardiorrespiratório 13 e do perfil antropométrico 14,15 .…”
Section: Level Of Physical Activity and Lipodystrophy Syndrome In Patunclassified
“…Considerando os treinamentos aeróbios e de força, foram localizados quatro estudos: Terry et al (24) , Smith et al (25) , Yarasheski et al (26) e Lindegaard et al (27) . Terry et al (24) <I> em estudo randomizado com 30 pacientes HIV positivos com uso de TARV e dislipidemia, verificaram o VO 2pico , a composição corporal, a contagem de T-CD4+, a carga viral e o perfil lipídico em um programa de exercícios aeróbios.…”
Section: Treinamentos Aeróbio E De Forçaunclassified